Efektivitas Satgas Pencegahan dan Penanganan Kekerasan Seksual di Kampus Universitas Nusa Cendana - Nuraini Kusuma Andriyani (Faculty of Social and Political Science, 2024)
Sexual violence on campus is gaining more attention, as more people are concerned about the need for a safe and inclusive space for all members of the academic community. The Indonesian government has taken steps by issuing Minister of Education, Culture, Research, and Technology Regulation No. 30 of 2021, which encourages the establishment of a Task Force for the Prevention and Handling of Sexual Violence (Satgas PPKS) in every university. This study aims to examine the extent to which the Satgas PPKS at Nusa Cendana University (UNDANA) has been successful in its duties, namely preventing, handling, and providing assistance to victims of sexual violence. This study uses a descriptive qualitative method based on a literature review, collecting various sources such as regulations, scientific articles, institutional reports, and media news. The results show that although the Satgas PPKS at UNDANA has carried out several initiatives such as socialization and reporting, there are still several obstacles, such as limited resources, a culture of resistance, a lack of ongoing training, and an inadequate reporting and protection system. Therefore, improvements in internal policies, the capabilities of Satgas members, and better financial and material support are needed so that the Satgas PPKS can work more effectively. This study recommends the importance of cooperation from various parties and placing the perspective of victims as the main basis in creating a campus free from sexual violence.